Synthesis of potential prebiotic α-glucooligosaccharides using microbial glucansucrase and their in vitro fecal fermentation. Issue 2 (7th February 2020) - Hu, Xiuting; Song, Liping; Yang, Yuqi; Jin, Zhengyu; Miao, Ming
Abstract : Novel α-glucooligosaccharides were synthesized by the acceptor reaction of Leuconostoc citreum SK24.002 glucansucrase with maltose and sucrose. Abstract : Novel α-glucooligosaccharides were synthesized by the acceptor reaction of Leuconostoc citreum SK24.002 glucansucrase with maltose and sucrose. The impact of synthesis conditions, including the ratio of sucrose to maltose and the substrate concentration, on the formation of α-glucooligosaccharides was evaluated. Under the optimized experimental conditions, the yield of a mixture of α-glucooligosaccharides with DP 3–5 reached approximately 56.4% with a concentration of 170.7 mg mL −1 . Each of these α-glucooligosaccharides was purified, and the structures were assigned as follows: α-D-Glc p -(1, 6)-α-D-Glc p -(1, 4)-D-Gl cp (DP3), α-D-Glc p -(1, 3)-α-D-Glc p -(1, 6)-α-D-Glc p -(1, 4)-D-Glc p (DP4), and α-D-Glc p -(1, 6)-α-D-Glc p -(1, 3)-α-D-Glc p -(1, 6)-α-D-Glc p -(1, 4)-D-Glc p (DP5), respectively. For these three structurally different oligosaccharides, the fermentation selectivity by fecal bacteria was determined in anaerobic batch culture. Fructooligosaccharide (FOS) was used as a positive prebiotic control. Similar to FOS, all three α-glucooligosaccharides selectively stimulated the proliferation of Bifidobacteria and Lactobacilli compared with the control. DP3 exhibited the strongest prebiotic ability to increase the Bifidobacterium and Lactobacillus population, whereas DP5 produced the most short-chain fatty acids. In addition, DP4 produced the highest butyrate concentration and resulted in the lowest acetate : propionate ratio. These results suggested that the enzymatically synthesized α-glucooligosaccharides were potential prebiotics, underlining correlations between the structural features of oligosaccharides and their impact on the metabolism of fecal microbiota.